2016
DOI: 10.1158/1541-7786.mcr-16-0003
|View full text |Cite
|
Sign up to set email alerts
|

Understanding TERT Promoter Mutations: A Common Path to Immortality

Abstract: Telomerase (TERT) activation is fundamental step in tumorigenesis. By maintaining telomere length, telomerase relieves a main barrier on cellular lifespan, enabling limitless proliferation driven by oncogenes. The recently discovered, highly recurrent mutations in the promoter of TERT are found in over 50 cancer types, and are the most common mutation in many cancers. Transcriptional activation of TERT, via promoter mutation or other mechanisms, is the rate-limiting step in production of active telomerase. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
226
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(252 citation statements)
references
References 143 publications
(116 reference statements)
8
226
0
2
Order By: Relevance
“…For example, although Simon and colleagues found no differences in frequency of MGMT methylation between pTERT mutant and wild-type tumors, the researchers did not differentiate between C228T and C250T mutations (9). This is perhaps reasonable as both hotspot mutations are known to generate an identical Ets/TCF transcription factorbinding motif (37)(38)(39). Very recently, however, functional differences between the C228T and C250T mutations with respect to NF-kB pathway activation has been reported (40).…”
Section: Discussionmentioning
confidence: 97%
“…For example, although Simon and colleagues found no differences in frequency of MGMT methylation between pTERT mutant and wild-type tumors, the researchers did not differentiate between C228T and C250T mutations (9). This is perhaps reasonable as both hotspot mutations are known to generate an identical Ets/TCF transcription factorbinding motif (37)(38)(39). Very recently, however, functional differences between the C228T and C250T mutations with respect to NF-kB pathway activation has been reported (40).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the TERT expression in these cells was comparable to that found in cancer cells and could signifi cantly delay telomere shortening-induced senescence. Furthermore, the high frequency of mutations in the TERT promoter mostly at two nucleotide positions (-146C>T, Long-distance elements -124C>T) strongly implicates them as driver events, appearing upon tumor initiation or possibly later in tumor development ( 27,28 ).…”
Section: Discussionmentioning
confidence: 99%
“…[45][46][47][48][49][50] More than 50 tumor types have now been shown to bear these hotspot mutations, and they often occur as an early driving step in tumorigenesis. 51 hTERT promoter mutations may additionally bear value as prognostic and diagnostic biomarkers insofar as they have been shown to be associated with decreased overall survival and aggressive histotypes in many cancers. 51 Through a G-to-A mutation (G/A) in the antisense strand, hTERT promoter mutations are proposed to generate an ETS/TCF element (CCGGAA) that would increase binding of the ETS transcription factor for activation of hTERT transcription.…”
Section: Introductionmentioning
confidence: 99%
“…51 hTERT promoter mutations may additionally bear value as prognostic and diagnostic biomarkers insofar as they have been shown to be associated with decreased overall survival and aggressive histotypes in many cancers. 51 Through a G-to-A mutation (G/A) in the antisense strand, hTERT promoter mutations are proposed to generate an ETS/TCF element (CCGGAA) that would increase binding of the ETS transcription factor for activation of hTERT transcription. 45,46 In addition, it has recently been suggested that the mutations found in glioblastoma multiforme could lead to recruitment of multimeric GA-binding protein (GABP) transcription factors to activate hTERT.…”
Section: Introductionmentioning
confidence: 99%